Patient perceptions and knowledge of corticosteroid injections: A cross-sectional survey study - Juliet Chung; Sina Ramtin; Philip Koehler; Stephen Stache; Charles Langman; Brian Hozack; Asif M. Ilyas (PLoS ONE, 2026)
Introduction Although cortisone injections are commonly used, patient understanding of cortisone is variable and often affected by misconceptions. This study explores patient perspectives, identifies misconceptions, and emphasizes the importance of improved patient education to enhance patient-centered care. Methods A cross-sectional survey study was conducted from April to August 2024 among patients aged 18 and older presenting to an orthopedic physicians’ office. Patients completed a novel anonymous questionnaire designed to assess their knowledge and perceptions of cortisone injections. A total of 246 patients participated, with responses collected electronically via SurveyMonkey. Results Among 246 respondents, individuals with history of prior cortisone infections were significantly more likely to correctly identify its anti-inflammatory role (p < 0.05). Overall, 96% of respondents reported awareness of cortisone injections. However, many learned from personal connections rather than healthcare professionals as their primary source of information Most respondents (87%) reported receiving satisfactory explanations from their physicians, while 13% reported inadequate communication. A majority indicated willingness to receive cortisone injections if clinically indicated (84%). Despite this,concerns regarding safety persist, with 37% associating safety with dosage and injection frequency, and 15% reporting uncertainty about potential risks. Conclusion Misconceptions regarding cortisone injections remain prevalent, highlighting gaps in patient understanding. Although most patients recognize the anti-inflammatory effects of cortisone, knowledge deficits persist regarding safe dosing parameters and potential risks. Improved communication between healthcare providers and patients about cortisone’s mechanism of action and safety profile may support more informed clinical decision-making and outcomes.